Metabolite and light regulation of metabolism in plants: lessons from the study of a single biochemical pathway - Oliveira,I.C. (2001)
We are using molecular, biochemical, and genetic approaches to study the structural and regulatory genes controlling the assimilation of inorganic nitrogen into the amino acids glutamine, glutamate, aspartate and asparagine. These amino acids serve as the principal nitrogen-transport amino acids in most crop and higher plants including Arabidopsis thaliana. We have begun to investigate the regulatory mechanisms controlling nitrogen assimilation into these amino acids in plants using molecular and genetic approaches in Arabidopsis. The synthesis of the amide amino acids glutamine and asparagine is subject to tight regulation in response to environmental factors such as light and to metabolic factors such as sucrose and amino acids. For instance, light induces the expression of glutamine synthetase (GLN2) and represses expression of asparagine synthetase (ASN1) genes. This reciprocal regulation of GLN2 and ASN1 genes by light is reflected at the level of transcription and at the level of glutamine and asparagine biosynthesis. Moreover, we have shown that the regulation of these genes is also reciprocally controlled by both organic nitrogen and carbon metabolites. We have recently used a reverse genetic approach to study putative components of such metabolic sensing mechanisms in plants that may be conserved in evolution. These components include an Arabidopsis homolog for a glutamate receptor gene originally found in animal systems and a plant PII gene, which is a homolog of a component of the bacterial Ntr system. Based on our observations on the biology of both structural and regulatory genes of the nitrogen assimilatory pathway, we have developed a model for metabolic control of the genes involved in the nitrogen assimilatory pathway in plants.